From monuments to traces : artifacts of German memory, 1870-1990 - Koshar, Rudy (Weimar and now, 2000)
This text constructs a framework in which to examine the subject of German collective memory, which for more than half a century has been shaped by the experience of Nazism, World War II and the Holocaust. Beginning with national unification in 1870-71 it follows through to reunification in 1990.